Do balbucio às primeiras palavras: continuidade e descontinuidade no devir de um falante - Milano, Luiza; Flores, Valdir do Nascimento (Letras de Hoje, 2015)
Este trabalho propõe reler o texto de Roman Jakobson Por que “mama” e “papa”? com o intuito de retomar a hipótese da descontinuidade relativa à passagem do balbucio ao sistema fonológico de uma dada língua. Assume-se que, do ponto de vista da interlocução, a “fala de bebê” indica, nessa passagem, uma relação simultânea entre continuidade e descontinuidade. Defende-se, ainda, que, nessa simultaneidade, aspectos físico, fisiológico, cognitivo, psíquico e linguístico encontram sentido na “fala de bebê”, o que permite a passagem do homem da condição de infans à de falante. ************************************************************************************************************************************************************************************************************ From babbling to the first words: continuity and discontinuity in the process of becoming a speaker Abstract: This paper suggests a different reading of Roman Jakobson’s text Why “mama” and “papa”?, aiming to reexamine the hypothesis of relative discontinuity in the passage from babbling to the phonological system of a given language. It is assumed that in this passage, from the standpoint of interlocution, the “baby talk” indicates a simultaneous relationship between continuity and discontinuity. It is also argued that in this simultaneity physical, physiological, cognitive, psychic, and linguistic aspects find meaning in the “baby talk”, which enables an individual to go from the condition of infans to speaker. Keywords: Babble; Continuity; Discontinuity; Interaction; Language acquisition